Redefining Appraisal: Giving Teachers Ownership of their Practice - Janelle McKenzie (New Zealand Journal of Teachers' Work)
Appraisal has, for many years, been seen as something ‘done’ to teachers. It has simply been that bit extra that needed to be completed each year to ensure teachers could teach one more year. It was seen as having little benefit or significance, simply being a ‘tick box’ exercise. This article reports on a study aimed to change this view and give teachers ownership of the appraisal process through self-directed professional development within a collaborative and collegial environment. The study demonstrated the need for teachers to direct their own professional development and learning within an open and supportive environment where they felt safe to ‘take a chance’. In enabling and supporting teachers to do this, a structured portfolio ‘skeleton’ was developed. Teachers were then able to ‘flesh out’ and personalise their portfolios in order to demonstrate their individual professional practice.